Functiones et Approximatio. Commentarii Mathematici - Kaczorowski, Jerzy (Wydawnictwo Naukowe UAM, 2016)
Functiones et Approximatio, Commentarii Mathematici jest czasopismem matematycznym wydawanym od 1974 roku przez Wydział Matematyki i Informatyki Uniwersytetu im. Adama Mickiewicza w Poznaniu. Każdy zeszyt zawiera oryginalne prace matematyczne z zakresu szeroko rozumianej analizy i teorii liczb.

Functiones et Approximatio, Commentarii Mathematici is a mathematical journal edited by the Faculty of Mathematics and Computer Science of Adam Mickiewicz University since 1974. The journal publishes original papers in mathematics, with special attention to analysis (in a broad sense) and number theory.
Keywords: analiza i teoria liczb